Benchmarking carbon emissions efficiency in Chinese cities: A comparative study based on high-resolution gridded data. (15th May 2019) - Cai, Bofeng; Guo, Huanxiu; Ma, Zipeng; Wang, Zhixuan; Dhakal, Shobhakar; Cao, Libin
Highlights: A high spatial resolution CO2 emissions inventory of 280 Chinese cities was compiled. Three methods were compared to evaluate the carbon efficiency of Chinese cities. The best and worst-performing cities were consistent regardless of different methods. Top-ranking cities were located in the coastal regions of China. Lagging-behind cities were located in the central and western regions of China. Abstract: Comprehensive and accurate city-level carbon dioxide emissions inventory is key to success in China's pursuit of low-carbon development. Based on a high-resolution gridded data, this paper evaluates and benchmarks the carbon emissions efficiency of 280 Chinese cities using three different methods, i.e., composite index, data envelopment analysis and stochastic frontier analysis. The comparative analysis reveals that the average carbon emissions efficiency of Chinese cities is about 70–90%, with only 9 efficient cities (3%). Although the ranking of intermediate cities varies greatly according to the method employed, the most and least carbon-efficient cities remain consistent. While the best-performing cities are found in the coastal regions, the worst-performing cities are located in the central and western regions, which suggests an imbalanced low-carbon development in China. Guided by the results, local governments are encouraged to compete and learn from similar ranking benchmarks in a new regime of "Top Runner City". Finally, the scores of carbon emissions efficiency can provide a scientific basis for the bottom-up allocation of carbon emissions rights to boost the development of the nationwide carbon market in China.